2015
DOI: 10.2215/cjn.09981014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lisinopril and Atenolol on Aortic Stiffness in Patients on Hemodialysis

Abstract: Background and objectives Whether improvements in arterial compliance with BP lowering are because of BP reduction alone or if pleiotropic effects of antihypertensive agents contribute remains unclear. It was hypothesized that, among patients on hemodialysis, compared with a b-blocker (atenolol), a lisinopril-based therapy will better reduce arterial stiffness.Design, setting, participants, & measurements Among 200 participants of the Hypertension in Hemodialysis Patients Treated with Atenolol or Lisinopril Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Although currently there are no medications that specifically target PP, a marker of arterial stiffness, a recent clinical trial of HD patients reported that atenolol was superior to lisinopril in improving arterial stiffness. 45 Thus, understanding the relationship of various BP components with outcomes among HD patients may help in selection of appropriate BP medications as more therapies emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Although currently there are no medications that specifically target PP, a marker of arterial stiffness, a recent clinical trial of HD patients reported that atenolol was superior to lisinopril in improving arterial stiffness. 45 Thus, understanding the relationship of various BP components with outcomes among HD patients may help in selection of appropriate BP medications as more therapies emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings mainly targeting the non-dialysis population confirmed our results in dialysis patients. Additionally, β-blockers were superior in improving arterial stiffness, left ventricular function, and long-term control of hypertension in dialysis patients so that they were able to reduce malignant cardiovascular events [39][40][41]. In this systematic review, data regarding incorporated RCTs displayed that the benefits of β-blockers for all-cause mortality, cardiovascular mortality, cardiovascular events, and hospitalizations in dialysis patients were similar to those in people who did not receive dialysis.…”
Section: Discussionmentioning
confidence: 79%
“…Third, we acknowledge that the follow-up period of 2 years is relatively short for cardiovascular outcome parameters. Our study was designed to study the effect of vitamin B12 and folic acid supplementation on PWV, and for this parameter, a 2-year intervention is considered to be sufficient, because PWV is known to respond quickly as other trials with PWV as outcome variable have shown [8,29,30]. Nevertheless, arterial stiffness is known for its limited reversibility and therefore it cannot be ruled out that differences in PWV levels may have been detected when using a longer intervention period.…”
Section: Discussionmentioning
confidence: 99%